Peran Desain Fisik Kelas dalam Pembelajaran IPAS Berbasis Budaya Lokal Bondowoso di Kelas V SDN Dabasah 1 - Salma Firdausi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
One way to improve education in Indonesia is by improving success factors in learning. Classroom design is one of the keys to successful learning. Psychologically, classroom design affects students' activeness and interest in the learning process. The research used is qualitative research using descriptive analysis method through field research. Describing a thing as it is, so that it gives a clear picture of the situation in the field. Qualitative research is used because qualitative research can answer the problems that arise. Sources of data in the study are words and actions, apart from that it is additional data such as other documents. The U-shaped classroom design was implemented in accordance with the research objectives, namely making it easier for students to recognize and understand the local culture of their own region. The new classroom design makes it easier for students to explore the classroom well, makes it easier for students to interact with other students, and makes it easier for students to recognize and understand the local culture of Bondowoso. Based on the results of the research, it can be concluded that the new classroom design makes it easier for students to understand learning, recognize Bondowoso's local culture, and makes it easier for teachers to supervise students during learning.
Repo 21 Juli 2026_ Rudy K Finalisasi 21 Juli 2026_Yudi
Keywords: Bondowoso Culture; Class Design; & Local Culture.